Sensory trial of camel milk powder among pastoralist communities of the Somali Region, Ethiopia - Ahmed Mohammed Ibrahim; Seid Mohammed Ali; Yahya Maidane Osman; Fathiya Budul Ismail; Mohamed Omar Osman; Pauline Rouchon; Mukhtar Harir Hussein; Abdifatah Muktar Muhummed; Ramadan Budul Yusuf; Raymond Place; Jan Hattendorf; Rea Tschopp; et al. (PLoS ONE, 2025)
Background Camel milk is a vital source of nutrition for people living in many arid and semi-arid regions. Camel milk powder offers a valuable opportunity for the dairy industry to develop and launch innovative products in the milk and dairy market. Objective To evaluate the sensory preference of camel milk powder compared to fresh camel milk among pastoralist communities in the Somali Region of Ethiopia. Methods A single-blinded sensory crossover study was conducted among randomly selected 248 pastoralist communities in the Somali Region. Data were collected using structured questionnaires. Participants did not know whether they tasted fresh milk or camel milk powder. The sequence was randomized, assigning either fresh/camel milk powder or powdered/fresh camel milk to each participant. Data was summarized using mean, median, frequency, and percentage and was presented using charts and tables. Bi-variable and multivariable binary logistic regression were used to identify variables associated with the outcome. Statistical associations were assessed using odds ratios and 95% confidence intervals, with significance declared at a P-value < 0.05. A t-test was used to compare milk spending and milk liking levels between powdered and fresh camel milk. Results In this study, 31% (95% CI: 25.5%–37.1%) preferred powdered milk among pastoralists in the Somali Region. Factors significantly associated with preference of camel milk powder included being an urban pastoralist resident, AOR = 2.02 (95% CI: 1.30, 3.16), and being female, AOR = 1.94 (95% CI: 1.25, 3.01). There is no statistically significant mean difference between fresh camel milk and camel milk powder regarding willingness to pay. Conclusion Although most preferred fresh milk, the mean rating of powder was still high. Powdered milk might be a good alternative in settings where a cold chain is difficult to maintain and shelf life is an issue. Factors such as place of residence and sex of pastoralist significantly influence preference of powdered milk. There is no significant difference in willingness to pay between fresh camel milk and powdered camel milk. Focusing on nutritional advantages, safety, and convenience regarding camel milk powder is crucial for rural and male pastoralists’ adoption. Promotional efforts should be improved in accessibility and practicality without reducing cost.